Stress of COVID-19, Anxiety, Economic Insecurity, and Mental Health Literacy: A Structural Equation Modeling Approach - Hu, Yangxiu; Ye, Baojuan; Tan, Jiawen (Frontiers in Psychology, 2021)
The COVID-19 pandemic is currently a global health threat attributed to negatively affecting the mental health and well-being of people globally. The purpose of the current study is to examine the mediating role of economic insecurity and mental health literacy in the relationship of stress of COVID-19 and anxiety. Results from the current study using a large sample of Chinese college students (N = 1,334) showed that stress of COVID-19 was positively associated with economic insecurity and anxiety while negatively associated with mental health literacy, which in turn, was negatively associated with anxiety. These results elucidate our understanding of the role of mediators in stress of COVID-19 and anxiety. The findings are useful in terms of providing evidence for tailoring interventions and implementing preventative approaches to mitigate anxiety due to stress of COVID-19. Based on the present findings and within the context of COVID-19, the potential utility of promoting MHL to reduce the psychopathological consequences of COVID-19 is discussed.